Legal framework on gender equality in the workplace: Comparative study in Malaysia and India - Chin, Simone (2023)
Gender equality in the workplace has become a major issue worldwide. Women are still under-represented in leadership positions, and they continue to experience discrimination and bias at work despite progress in recent years. The legal framework that promotes gender equality in the workplace is one of the most important factors in addressing these issues. There have been several laws and policies implemented in Malaysia and India, two rapidly developing countries in the Asia-Pacific region, to address gender inequalities in their respective workforces. As part of this paper, a comparative analysis of Malaysian and Indian legal frameworks for gender equality at work is presented. This study examines the various laws and policies that promote gender equality in both countries and evaluates their effectiveness in promoting gender equality. The research identifies key challenges and gaps in both countries' legal frameworks that prevent progress toward gender equality at work. Additionally, the paper examines gender equality history in both countries. The research draws on primary and secondary sources of data including interviews, academic literature, government reports, and legal documents to provide a comprehensive understanding of the legal frameworks for gender equality in the workplace in Malaysia and India. The study concludes with recommendations to strengthen legal frameworks in both countries and promote gender equality in the workplace.